Use of Posidonia Oceanica Ash in Stabilization of Expansive Soils - Malekzadeh, Mona; Bilsel, Huriye (Taylor & Francis Inc, 2014)
Posidonia oceanica (PO) is the most plentiful seaweed of the Mediterranean Sea, which grows all along the coastal areas, forming widespread meadows. The leaf rejuvenation process of Posidonia oceanica typically occurs in fall when an increase in wave action causes the dead seaweeds to be transported and usually piled up along the coastal areas. This paper investigates the effect of PO ash stabilization on behaviour of an expansive clay. The ash was obtained by combustion of crushed PO pieces in a muffle furnace at 550 degrees C. Atterberg limits, linear shrinkage, particle size distribution, one-dimensional swell, and unconfined compression tests have been carried out on natural soil as well as soil mixtures with 5% and 10% PO ash. There has been no significant improvement in the soil properties with 5% ash inclusion, whereas 10% ash has noticeably reduced the swell amount and increased the compressive strength. It is therefore concluded that there is a potential for the use of PO ash in geotechnical engineering applications.
Keywords: one-dimensional swell; Posidonia oceanica; swelling soils; unconfined compressive strength